Implementation of Improving Human Resources Based on School Culture at SMPN 1 Pematangsiantar - Arif Rahman; Enjel Oktaviany Simanjuntak; Hilmi Saputri Nasution; Ribka Hernita Sitepu; Rosvina Sari Siburian (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the implementation of improving school culture-based human resources at SMPN 1 Pematangsiantar. The culture that exists in schools is actually able to become the basis for improving human resources. School culture is closely related to the values, vision and mission of the school that have been built and agreed upon by the school. This research was conducted within the framework of a qualitative research approach. A qualitative research approach is a process followed to explain perceptions and cases about a matter in a way that reflects the truth in their typical environment and as a whole using various data collection techniques such as observation, interviews, and document analysis. The results of the study revealed that the hallmark or characteristics of SMPN 1 Pematangsiantar, North Sumatra Province, namely, based on discipline and being a school of character in forming a cadre of national leaders who are patriotic, have national insight, culture, independence, who are competitive in the fields of science and technology. technology, and skills within the framework of faith and piety have been transformed into a school culture which then contributes to the improvement of human resources. High discipline is one of the advantages of SMP Negeri 1 Pematangsiantar to improve human resources